Aggravating Factors Influencing Physicians’ Employed in Public Medical Entities – Evidence from Poland - Julianna STASICKA; Beata SKOWRON-MIELNIK (Communications of International Proceedings, 2021)
Medical personnel are a group of employees particularly exposed to health hazards which arise from stress factors related to the place and specificity of work. Therefore, it is necessary to identify hazardous factors affecting workers’ health and try to limit their occurrence. Taking these measures into account is vital in connection with the observed deficit of medical staff. Based on the analysis of literature, empirical studies were conducted to determine the significance of factors burdening physicians in relation to their employment in medical entities. The main goal of this research was to identify key aggravating factors in the work of the youngest groups of people practicing medical professions – medical residents and medical students – basing on their subjective experiences. The context of this research is to provide employers with information necessary to implement measures in order to ensure a working environment favorable for new, young employees taking up employment in public hospitals in Poland. To this end, a survey was conducted in January 2020, using two separate questionnaires distributed among physicians and medical students on private groups on social networking sites. The answers provided by the respondents showed that working conditions in public health care entities in Poland are unfavorable and there are numerous aggravating factors, the main one being the constant burden of responsibility for the life and health of patients. Respondents also indicated that they experience bullying and aggression from patients, as well as pressure to perform their profession contrary to law or ethics. Based on results of the study, recommendations are proposed that can be implemented at the level of individual organizations.
Keywords: Aggravating Factors; Work Conditions; Health Care